2016
DOI: 10.1097/mpg.0000000000001230
|View full text |Cite
|
Sign up to set email alerts
|

Yoga Therapy for Abdominal Pain‐Related Functional Gastrointestinal Disorders in Children

Abstract: At 1-year follow-up, YT in addition to standard care was superior compared with SMC according to treatment success, PIS, and reduction of school absence. YT, however, was not significantly more effective in improving PFS or QoL, compared with SMC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 42 publications
4
36
0
1
Order By: Relevance
“…Nineteen studies were excluded, of which four were new to this update (Jastrowski Mano 2013; Korterink 2016; Rapoff 2014; Rutten 2017). We excluded Connelly 2006, Hicks 2006, Palermo 2009, Rapoff 2014, Stinson 2010, Trautmann 2010 as they were delivered remotely, so did not meet the new inclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nineteen studies were excluded, of which four were new to this update (Jastrowski Mano 2013; Korterink 2016; Rapoff 2014; Rutten 2017). We excluded Connelly 2006, Hicks 2006, Palermo 2009, Rapoff 2014, Stinson 2010, Trautmann 2010 as they were delivered remotely, so did not meet the new inclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
“…We excluded Connelly 2006, Hicks 2006, Palermo 2009, Rapoff 2014, Stinson 2010, Trautmann 2010 as they were delivered remotely, so did not meet the new inclusion criteria. Eight studies were excluded as they had fewer than 10 participants in a treatment arm at the end of treatment (Fentress 1986; Jastrowski Mano 2013; Kroener-Herwig 1998; Larsson 1986; Sanders 1989; Trautmann 2008; Weydert 2006; Youssef 2009), three studies were judged to have insufficient psychological content in the treatment (Koenig 2013; Korterink 2016; Olness 1987), one study reported only follow-up data of more than one year (Vlieger 2012), and one trial was had a non-inferiority design (Rutten 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Yoga therapy in children with FAP aims to reduce anxiety, improve tone and increase feelings of well-being 58. Korterink et al 59 looked at yoga therapy in 69 children aged 8–18 with ‘abdominal pain-related’ FGIDs, noting significant improvements in pain intensity scoring and school absence but not in pain frequency or quality of life. A recent Cochrane review concluded that there was no robust evidence for the effectiveness of yoga therapy 55…”
Section: Clinical Questionsmentioning
confidence: 99%
“…The intervention group improved significantly in the management of children’s symptoms [ 42 ]. Yoga could be considered a particular type of CBT; in some studies, yoga resulted in a significant reduction in pain intensity in children with FAP and IBS [ 43 ]. Although the evidence is not yet strong enough to recommend yoga as a treatment, it can nonetheless be utilized together with standard medical care when requested, as it is not at all harmful.…”
Section: Managementmentioning
confidence: 99%